Draft Genome Sequence of Corynebacterium variabile Mu292, Isolated from Munster, a French Smear-Ripened Cheese - Dugat-Bony, Eric (Genome Announc, 2016)
Here, we report the draft genome sequence of Corynebacterium variabile Mu292, which was originally isolated from the surface of Munster, a French smear-ripened cheese. This genome investigation will improve our knowledge on the molecular determinants potentially involved in the adaptation of this strain during the Munster-type cheese manufacturing process.